2005
DOI: 10.1017/s0266462305050646
|View full text |Cite
|
Sign up to set email alerts
|

Assessing quality of end-of-life hospital care in a southern European regional health service

Abstract: End-of-life in cancer patients was diagnosed too late. The quality of care in palliative care units and by home hospitalization service was better than that in conventional hospitalization. Nevertheless, there were areas for improvement in the three modalities of care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Strong opioids were used significantly less in general wards; however, usage was better than that reported in previous studies: Opioid usage in the last 48 h of life was 19-83% in general wards [4,9,21,22] and 55-85% in PCU [10,22,26,35]. However, fentanyl was far less used in general wards.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Strong opioids were used significantly less in general wards; however, usage was better than that reported in previous studies: Opioid usage in the last 48 h of life was 19-83% in general wards [4,9,21,22] and 55-85% in PCU [10,22,26,35]. However, fentanyl was far less used in general wards.…”
Section: Discussionmentioning
confidence: 57%
“…After publication of the SUPPORT study, many studies reported inadequacy of end-of-life treatment in general wards. Especially in the last 48 h of life, many patients received inappropriate life-sustaining treatment [4][5][6][7][8][9] and inadequate pain and symptom management [4][5][6][9][10][11]. The current status of end-of-life treatment should be investigated to improve the clinical care of dying hospitalized patients.…”
Section: Introductionmentioning
confidence: 99%
“…This increased the palliative care competence of the area and may be a reason why the prevalence of hospitalized palliative cancer patients decreased in the study period. Cancer patients' symptoms can indeed be improved by hospital based palliative care teams [13] and palliative home care can reduce the need for hospitalization in acute care hospitals if the care is provided by trained personnel [14].…”
Section: Discussionmentioning
confidence: 99%